Assessment of the Iowa River's South Fork watershed: Part 2. Conservation practices - Tomer, M.D; Moorman, T.B; James, D.E; Hadish, G; Rossi, C.G (Journal of soil and water conservation, 2008)
Documenting the types and extent of conservation practices in a watershed is necessary to determine their water quality impacts. A conservation practice inventory for the South Fork of the Iowa River, 85% in corn (Zea mays L.) and soybean [Glycine max L. (Merr.)] rotations, showed only 7% of cropland was managed using no-tillage. About 30% of cropland receives manure annually, prior to corn. Surface residue following soybean was usually inadequate (<30%), indicating a key management challenge. About 90% of fields with >34% highly erodible land, subject to USDA conservation compliance, indeed had erosion-control practices installed. Grassed waterways and riparian buffers were common edge-of-field practices, and highly erodible land fields near streams often had multiple practices and rotations including third crops. Yet, while most conservation practices are aimed at controlling runoff, tile drainage is the dominant hydrologic pathway. Resource management systems that address tile drainage as the primary route of nutrient loss need to be developed and encouraged. Better targeting of this pathway could include practices such as nutrient removal wetlands.